2019
DOI: 10.1002/gps.5109
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self‐harm in older adults: A national analysis of US emergency department visits and follow‐up care

Abstract: Objective To examine mental health care received by older adults following emergency department (ED) visits for deliberate self‐harm. Methods This retrospective cohort analysis examined 2015 Medicare claims for adults ≥65 years of age with ED visits for deliberate self‐harm (N = 16 495). We estimated adjusted risk ratios (ARR) for discharge disposition, ED coding of mental disorder, and 30‐day follow‐up mental health outpatient care. Results Most patients (76.9%) were hospitalized with lower likelihoods observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
9
0
2
Order By: Relevance
“…Depression is a well-recognized risk factor for late-life suicidal behavior (Cheung et al, 2017a;Hawton and Harriss, 2006;Lapierre et al, 2011;Murphy et al, 2012;Salib et al, 2001;Schmutte et al, 2019;Troya et al, 2019a;Tsoh et al, 2005). In this study, the depression diagnosis (HR = 3.02) included people with a depression diagnosis for their current stay, receiving active treatment, or monitored but no active treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression is a well-recognized risk factor for late-life suicidal behavior (Cheung et al, 2017a;Hawton and Harriss, 2006;Lapierre et al, 2011;Murphy et al, 2012;Salib et al, 2001;Schmutte et al, 2019;Troya et al, 2019a;Tsoh et al, 2005). In this study, the depression diagnosis (HR = 3.02) included people with a depression diagnosis for their current stay, receiving active treatment, or monitored but no active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous local studies have already established self-harm methods in older adults are mainly medication overdose (over 60%), laceration, and multiple means (Cheung et al, 2017a;Tan and Cheung, 2019). Although self-harm in older adults resembles suicide (Fässberg et al, 2019;Hawton and Harriss, 2008;Salib et al, 2001;Schmutte et al, 2019), recent qualitative studies suggested they occur along a spectrum of no-suicidal intent to high levels of intent (Troya et al, 2019b;Wand et al, 2018). It has been estimated that 73.5% of the subjects included in a late-life self-harm review reported suicidal intention (Troya et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults, there are common risk factors for self-harm and suicide, and self-harm is more likely to be lethal with greater reported intent to die (Fassberg et al, 2019;Schmutte et al, 2019). However, not all people who self-harm do so with suicidal intent, and the two groups may be distinct (DeJong et al, 2010), with the outcome of death following self-harm sometimes related to external factors rather than intent or another meaning of the behavior (Linden and Barnow, 1997).…”
Section: Longitudinal Big Data Needs To Meet the Individual To Inform...mentioning
confidence: 99%
“…However, we already know much about these population-level risk factors (Troya et al, 2019). Research in this field needs to delve deeper, and explore the clinical trajectories and broader outcomes of older adults who self-harm in combination with qualitative data derived from the individuals themselves.In older adults, there are common risk factors for self-harm and suicide, and self-harm is more likely to be lethal with greater reported intent to die (Fassberg et al, 2019;Schmutte et al, 2019). However, not all people who self-harm do so with suicidal intent, and the two groups may be distinct (DeJong et al, 2010), with the outcome of death following self-harm sometimes related to external factors rather than intent or another meaning of the behavior (Linden and Barnow, 1997).…”
mentioning
confidence: 99%